ANALISIS KESEIMBANGAN PENAWARAN DAN PERMINTAAN BERAS DI INDONESIA - Eri Yusnita Arvianti; Rikawanto Rikawanto (BUANA SAINS, 2010)
This study aims to analyze the stability of Indonesian rice supply and demand equilibrium system and to evaluate short-run and long-run impacts of price policy using Cobweb equilibrium model. The results show that in the short-run equilibrium of rice supply and demand deviates; however, in the long-run it is stable. These implication is price policy on agricultural inputs and output does not disturb Indonesian rice market. Therefore, the policy is still reasonable to be implemented